Chiral-odd gluon generalized parton distributions in the proton: A light-front quantization approach - Bolang Lin; Sreeraj Nair; Chandan Mondal; Siqi Xu; Zhi Hu; Pengxiang Zhang; Xingbo Zhao; James P. Vary (Physics Letters B)
Within the basis light-front quantization (BLFQ) framework, we evaluate the gluon chiral-odd generalized parton distributions (GPDs) inside the proton at zero skewness. We employ the light-front wave functions of the proton obtained from a light-front quantized Hamiltonian with quantum chromodynamics input using BLFQ. Our investigation encompasses both the valence Fock sector with three constituent quarks and an additional sector containing three quarks and a dynamical gluon. We analyze the gluon GPDs in the momentum space as well as in the transverse position space. We further present the gluon's generalized form factors derived from the Mellin moments of its chiral-odd GPDs. Using the proton transverse spin sum rule, we also present the x-dependence of the angular momentum carried by the polarized gluon and determine the relative contributions of quarks and the gluon to the transversity asymmetry.